Feasibility of Ultra-Rapid Exome Sequencing in Critically Ill Infants and Children With Suspected Monogenic Conditions in the Australian Public Health Care System. Issue 11 (November 2020) - Lunke, Sebastian; Eggers, Stefanie; Wilson, Meredith; Patel, Chirag; Barnett, Christopher P.; Pinner, Jason; Sandaradura, Sarah A.; Buckley, Michael F.; Krzesinski, Emma I.; de Silva, Michelle G.; Brett, Gemma R.; Boggs, Kirsten; et al.
Abstract : (Abstracted from JAMA 2020;323(24):2503–2511) Multiple studies have shown that genomic testing has a high diagnostic yield and an impact on clinical management for patients with suspected genetic conditions. Therefore, there has been a push worldwide to apply rapid genomic sequencing in critically ill neonatal and pediatric patients.